Notice for additional works of steel sheath removal for one foundation pile - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the notice for additional works of steel sheath removal for one foundation pile of BRACU new campus development project.